JURIDICAL ANALYSIS OF LOCAL GOVERNMENT AUTHORITY ON THE ESTABLISHMENT LOCAL REGULATIONS ECO-TOURISM DEVELOPMENT - Luh Putu Sudini; Made Wiryani (Diponegoro Law Review, 2022)
Peraturan Daerah (Perda) are actually formed in the context of implementing provincial/district/city regional autonomy and co-administration tasks, as well as further elaborating the provisions of higher laws and regulations. Ecotourism is a concept of nature-based travel. Law Number 23 of 2014 concerning Regional Government, regulates the affairs and authorities of the provinces, districts and cities. Tourism, environment and forestry affairs are concurrent government affairs, namely the authority is divided between the central government and local governments. Government support in developing ecotourism in the regions is stated in the Regulation of the Minister of Home Affairs Number 33 of 2009 regulating the development of ecotourism in the regions optimally. It needs a strategy of planning, utilization, control, institutional strengthening and community empowerment by taking into account social, economic principles and involving stakeholders interest. However, there are no regulations that more technically regulate the development of ecotourism in the regions. So, there is a vacuum of legal norms. Therefore, local governments have a central role in forming ecotourism regulations in accordance with the ecotourism resource potential of each region. The research was conducted on the problems at which local government level has the authority to form an ecotourism regional regulation and what is the process of its formation. This research uses normative legal research methods, statutory approach, conceptual approach. This study uses an analysis of the Theory of Authority, the elaboration of norms and legislation. The results of the study found that Ecotourism Regional Regulations can be formed by each level of Regional Government according to the government affairs and regional authorities concerned. The obstacle that occurs is that there are still many regions that do not have local regulations on the Master Plan of Regional Tourism Development. This causes the Dinas Pariwisata, Kepemudaan dan Olahraga (Dispaspora) of the area does not have the basis of legal authority to make a document Rencana Induk Pengembangan Parwisata Daerah (RIPPARDA) which serves as a guide to Tourism Management in the area.